MODEL ALAT PENGERING IKAN BERBASIS ARDUINO UNO DENGAN SENSOR SUHU LM35 UNTUK PEMBUAT IKAN ASIN DI KOTA KUPANG - SURBAKTI, JOI Alfreddi (TURBO [Tulisan Riset Berbasis Online], 2023)
The coastal area of Kupang City dries salted fish in the usual way, namely by using roofless drying areas in the form of racks or boards arranged around fishermen's houses. However, this method has a weakness: the drying process takes longer, namely 1 day to dry anchovies and 2 days to dry flying fish. If the weather is cloudy and rainy, drying time may take 3-5 days. The operating principle of this Arduino Uno-based automatic salted fish dryer is to use a heating element as the heat source for the dryer and a fan as a control for air circulation, followed by an LM35 temperature sensor to determine the temperature. Inside the dryer there is a 162 LCD screen that displays the drying value, temperature, menu, and drying time, then program the Arduino Uno as a microcontroller to operate the system. The design of this tool measures 40 cm high, 35 cm wide, and 45 cm long. It is equipped with 2 baking trays for drying fish, each tray can only accommodate 1/4 kg of fish. The test results from the entire research were carried out by drying two types of salted fish, namely flying fish and anchovies weighing 1/2 kg and 1/4 kg. The test results showed that drying flying fish took 2-3 hours and drying anchovies took 1- 2 hours